What is in the Neuromuscular Junction Literature?. Issue 4 (June 2022) - Al-Lahham, Tawfiq; Lacomis, David
Abstract: This update covers a number of treatment topics starting with Fc receptor inhibitors and the Federal Drug Administration approval of efgartigimod. Some uncertainties regarding the use of corticosteroids are addressed, namely the risk of exacerbation with initiation of treatment and how to taper. The presence and potential importance of antibody overshoot following plasmapheresis is noted and the evolving increase in usefulness of acetylcholine receptor antibodies in diagnosing ocular myasthenia. Several recent series and case reports regarding coronavirus 2019 and myasthenia gravis are reviewed. The topics of myasthenia gravis and pregnancy, and another look at thymectomy in MG are provided. Finally, a couple of case reports on Lambert-Eaton myasthenic syndrome concentrate on the ice pack test and an autoantibody association with paraneoplastic cerebellar degeneration and Lambert–Eaton myasthenic syndrome in the same patient.